Integrating Sustainability Accounting into Javanese Wedding Rituals: A Symbolic and Financial Analysis of the Siraman and Midodareni Processions - Rahmawati, Yunaita; Amri, Muhtadin; Wahyuni, Ajeng; Nurhidayati, Maulida (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to explore the symbolism and meaning of the siraman and midodareni processions in the context of social and cultural sustainability in Javanese society. This study also integrates simulated financial data to reflect the economic and social contributions of these rituals within the framework of sustainability accounting. Using a qualitative research approach with a postmodern paradigm, this study explores the dynamics of cultural meanings that have adapted to the development of the times. The data sources for this study came from in-depth interviews with informants including traditional leaders, the bride and groom's family, and Javanese cultural figures. The results of the study show three main findings: first, the symbolism and meaning of social and cultural sustainability in the siraman and midodareni processions; second, the shift in meaning and adaptation of the siraman and midodareni processions; third, the positive impact of the siraman and midodareni processions in strengthening cultural identity and social sustainability. These findings contribute to the understanding of sustainability accounting in the preservation of sustainable local cultural values, besides enriches sustainability accounting literature by demonstrating how indigenous cultural practices can be documented and analyzed through both symbolic and quantitative approaches.